2014
DOI: 10.3846/20294913.2014.869514
|View full text |Cite
|
Sign up to set email alerts
|

Can Investment in Microfinance Funds Improve Risk-Return Characteristics of a Portfolio?

Abstract: This article is concerned with contribution of microfinance investment funds to a sustainable financial portfolio. With regard to the dependence of microfinance funds' returns on the performance of stock and fixed income markets in developed and emerging economies we find slightly negative correlation when measured by the portfolio beta measure. Our regression analysis confirms that returns on investment in microfinance investment funds exceed the returns on the market portfolio. This result together with repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 39 publications
0
7
0
1
Order By: Relevance
“…According to this theory, the "Trend Stabilizer" feedback prolongs the trends on average, and the "Price Inertia Feedback" forces the price towards the price level, which is given for example by the important economic news. Further momentum studies are provided by Pesaran and Timmermann (1995), Chan et al (1996), Divis and Teply (2005), Chang et al (2010), Stankevičienė and Gembickaja (2012), Janda and Svárovská (2013), Janda et al (2014), Barak et al (2015). Momentum and level trading methods are currently used in high frequency (HTF) algorithmic methods.…”
Section: Literature Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…According to this theory, the "Trend Stabilizer" feedback prolongs the trends on average, and the "Price Inertia Feedback" forces the price towards the price level, which is given for example by the important economic news. Further momentum studies are provided by Pesaran and Timmermann (1995), Chan et al (1996), Divis and Teply (2005), Chang et al (2010), Stankevičienė and Gembickaja (2012), Janda and Svárovská (2013), Janda et al (2014), Barak et al (2015). Momentum and level trading methods are currently used in high frequency (HTF) algorithmic methods.…”
Section: Literature Overviewmentioning
confidence: 99%
“…The first crucial finding of this research is based on a simple spectrum or spectrogram of the price development. In most cases, a realistic spectrum is not so optimistic for significant cycles as in Kaufman (2013) in Figure 3.…”
Section: Findings Of the Research On The Fourier Analysismentioning
confidence: 99%
“…Cernohorska et al (2012) constructed a new market liquidity index based on the calculation of using traditional indicators of market depth, resiliency, tightness, volatility and liquidity for money, foreign exchange, bond and stock markets. Janda and Svárovská (2013) and Janda et al (2014) investigated microfinance investment funds and found that in time, these funds provided modest but stable returns compared to benchmark market indices. Primbs and Rathinam (2009) modelled extraneous, value, momentum and hedge traders and explored the effects these trading strategies may have on price dynamics.…”
Section: Introductionmentioning
confidence: 97%
“…In Pakistan few private commercial banks have transformed into MFIs. However, in other countries like Nepal, Thailand and Malaysia there are several projects for transforming commercial banks into MFIs (Dokulilova, 2009;Janda et al, 2014;Krauss, 2011).…”
Section: Introductionmentioning
confidence: 99%